2005
DOI: 10.1188/05.onf.250-256
|View full text |Cite
|
Sign up to set email alerts
|

Post-Treatment Symptoms Among Ethnic Minority Breast Cancer Survivors

Abstract: A need exists for affordable, culturally appropriate symptom management interventions. Nursing will have a vital role in designing, testing, and offering such interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
134
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(158 citation statements)
references
References 28 publications
20
134
0
3
Order By: Relevance
“…Depression was most frequently associated with fatigue (Bower et al, 2000;Den Oudsten et al, 2009;Vahdaninia et al, 2010) followed by lower income/poor financial status (Eversley et al, 2005;Morrill et al, 2008;Chen et al, 2009), low education (Mehnert and Koch, 2008;Morrill et al, 2008;Alcalar et al, 2012) and younger age (Broeckel et al, 2000;Mehnert and Koch, 2008). Regarding marital status, being unmarried (Broeckel et al, 2000;Morrill et al, 2008), widowed or divorced (Chen et al, 2009) were significantly associated with depression although in contrast with one study which found being married (Pumo et al, 2012) was associated with depression.…”
Section: Factors Associated With Depressionmentioning
confidence: 75%
See 1 more Smart Citation
“…Depression was most frequently associated with fatigue (Bower et al, 2000;Den Oudsten et al, 2009;Vahdaninia et al, 2010) followed by lower income/poor financial status (Eversley et al, 2005;Morrill et al, 2008;Chen et al, 2009), low education (Mehnert and Koch, 2008;Morrill et al, 2008;Alcalar et al, 2012) and younger age (Broeckel et al, 2000;Mehnert and Koch, 2008). Regarding marital status, being unmarried (Broeckel et al, 2000;Morrill et al, 2008), widowed or divorced (Chen et al, 2009) were significantly associated with depression although in contrast with one study which found being married (Pumo et al, 2012) was associated with depression.…”
Section: Factors Associated With Depressionmentioning
confidence: 75%
“…Factors related to treatment of breast cancer reported to be significantly associated with depression included more time elapsed since the end of chemotherapy (Broeckel et al, 2000), receiving chemotherapy (Eversley et al, 2005;Morrill et al, 2008), had mastectomy (Eversley et al, 2005), had breast conserving type of surgery (Den Oudsten et al, 2009) and using an alternative treatment (Karakoyun-Celik et al, 2010).…”
Section: Factors Associated With Depressionmentioning
confidence: 99%
“…The intensive, multi-modality treatments of chemotherapy drugs, radiation and surgery that have improved cancer survival often produce disruptive side effects that unexpectedly interfere with the patient's physical and mental functioning affecting their everyday QOL. [3][4][5] Often these disruptions may manifest themselves as perceived unmet needs that affect not only the individual's QOL but can also affect compliance to treatment regimens and thus impact individual long-term prognosis. As Puerto Ricans are one of the largest Hispanics groups in the US, [6,7] it is crucial that clinicians and researchers become skilled in assessing the prevalence of the perceived unmet needs of Puerto Rican cancer patients undergoing treatment to properly respond to their needs.…”
Section: Introductionmentioning
confidence: 99%
“…The level of depression may vary from moderate to severe 43,44 and severity may correlate with the stage of the disease at diagnosis. 45 It is suggested that depression can be assessed using predictors of self-esteem, level of social support and fatigue and can be alleviated through measuring the association between the biological, psychological and social dimensions of experience of breast cancer.…”
mentioning
confidence: 99%